Malignant Fibrous Histiocytoma of the Breast: A Case Report - Dimosthenis Miliaras; Emmanouel Konstantinides (Hindawi Limited, 2012)
This paper concerns a case of Malignant Fibrous Histiocytoma (MFH) of the Breast in a 73-years-old woman. A lump was found in her right breast, measuring 1.7 cm in diameter. Surgical excision followed, and pathology revealed a highly atypical spindle cell tumor. Immunohistochemistry along the histological features, excluded the possibility of carcinoma, malignant phyllodes tumor, or another type of pure sarcoma. There was no history of previous irradiation in the region. MFH is among the rarest types of sarcoma of the breast, and most of the times behaves aggressively. Excision with wide, free-of-tumor margins is the most effective treatment, when feasible.